The Influence of Tabata Training and Interval Training on VO2max Endurance Improvement in Pencak Silat Martial Arts Athletes - Muawanah, Elok Nur Akhiroh; Nasuka, Nasuka; Hadi, Hadi; Yudhistira, Dewangga (Indonesian Journal of Sport Management, 2025)
The purpose of this study is to examine how interval and tabata training affect the improvement of VO2 max endurance in pencak silat athletes. This study uses a pre-experimental design. The Multi-stage Fitness Test (MFT) is the measurement instrument used in this study, employing a two-group pre-test and post-test design. The study involved a total of 14 athletes from the Central Java Pencak Silat PPLOP, divided into two groups, each consisting of 7 athletes. The results show that both training methods significantly improve the athletes' VO2 max endurance. Based on the SPSS series 26 data analysis, it was found that: 1. Tabata training has a significant effect on the VO2 max endurance results of pencak silat athletes with a p-value of 0.004 < (p<0.05). 2. Interval training has a significant effect on the VO2 max endurance results of pencak silat athletes with a p-value of 0.000 < (p<0.05). 3. There is a significant difference between the two training methods in terms of VO2 max endurance results in pencak silat athletes. However, based on the final Paired Sample T-Test, VO2 max improvement was more significantly influenced by Tabata training compared to interval training. The average VO2 max improvement in the Tabata group was 5.4000, while in the Interval Training group it was 4.9714. This study provides practical implications for designing more effective training programs to improve the aerobic endurance capacity of athletes. Future research is recommended to use a larger sample size and consider other factors that may influence training outcomes.